1998
DOI: 10.1089/ten.1998.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Differentiation of Three-Dimensional Rat Marrow Stromal Cell Culture on Microcarriers in a Rotating-Wall Vessel

Abstract: Using a high aspect ratio vessel (HARV), this study investigated the formation of 3-D rat marrow stromal cell culture on microcarriers and the expression of bone-related biochemical markers under conditions of simulated microgravity. In addition, it calculated the shear stresses imparted on the surface of microcarriers of different densities by the medium fluid in an HARV. Secondary rat marrow stromal cells were cultured on two types of microcarriers, Cytodex-3 beads and modified bioactive glass particles. Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…[7][8][9] We previously reported that 3D poly(glycolic acid) (PGA) meshes supported the formation of cartilaginous and bone-like tissues by avian BMSC expanded in the presence of fibroblast growth factor-2 (FGF-2). 10 However, mammalian (bo-vine calf) BMSC cultured on PGA meshes under the same conditions failed to differentiate over 4 weeks in vitro and cell-polymer constructs collapsed.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] We previously reported that 3D poly(glycolic acid) (PGA) meshes supported the formation of cartilaginous and bone-like tissues by avian BMSC expanded in the presence of fibroblast growth factor-2 (FGF-2). 10 However, mammalian (bo-vine calf) BMSC cultured on PGA meshes under the same conditions failed to differentiate over 4 weeks in vitro and cell-polymer constructs collapsed.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the drawbacks associated with static culturing systems, considerable interest has been generated in tissue engineering by using the high-aspect-ratio vessel rotating bioreactor, which has the characteristic of low-shear, three dimensionality and highmass transfer and thus provides a dynamic flow culture condition to promote tissue synthesis (18)(19)(20)(21). Various cell types can form 3D assemblies in the rotating bioreactors (22)(23)(24)(25)(26). Rat stromal cells cultured on cytodex-3 beads have been shown to form aggregates and synthesize mineralized matrix, and cell aggregates formed by MC3T3 osteoblast-like cells produced collagen fibrils in the matrix between microspheres (17).…”
mentioning
confidence: 99%
“…To overcome such limitations, Ducheyne and co-workers (Qiu et al, 1998(Qiu et al, , 2000(Qiu et al, , 2001) envisioned a strategy using the HARV bioreactor and microcarriers to engineer constructs that could be used for bone TE purposes. In a first approach, the authors used bioactive glass, Cytodex-3 beads and rat stromal cells for assessing the feasibility of culture using a HARV bioreactor (Qiu et al, 1998).…”
Section: Microparticle-based Systems In Hybrid Cell-materials Constructsmentioning
confidence: 99%
“…To overcome such limitations, Ducheyne and co-workers (Qiu et al, 1998(Qiu et al, , 2000(Qiu et al, , 2001) envisioned a strategy using the HARV bioreactor and microcarriers to engineer constructs that could be used for bone TE purposes. In a first approach, the authors used bioactive glass, Cytodex-3 beads and rat stromal cells for assessing the feasibility of culture using a HARV bioreactor (Qiu et al, 1998). It was observed that 3D multicellular aggregates consisting of multiple cell-covered Cytodex-3 microcarriers bridged together, as well as mineralization taking place, and the expressions of alkaline phosphatase activity, collagen type I, and osteopontin were shown (Qiu et al, 1998).…”
Section: Microparticle-based Systems In Hybrid Cell-materials Constructsmentioning
confidence: 99%
See 1 more Smart Citation